2008 13th International Conference on Harmonics and Quality of Power 2008
DOI: 10.1109/ichqp.2008.4668777
|View full text |Cite
|
Sign up to set email alerts
|

ATP on the impact analysis of an independent power producer in a distribution network

Abstract: The main task in this paper is to present a performance analysis of a distribution network in the presence of a synchronous generator with its speed and voltage regulators, in parallel with the distribution system, for distributed generation studies. Must be highlighted that this generator is driven by a steam turbine, and the whole system with regulators and the equivalent of the power authority system in the point of connection are modeled in the "ATP -Alternative Transients Program". Technical questions stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, in such references a simpler voltage regulator model was used. It can be observed that the results obtained in [10,11] are more oscillatory. This fact was not present in the simulations made here, due to the fact that a more efficient voltage regulator model was used, showing that in previous studies the results obtained had pessimistic responses.…”
Section: Load Rejection At the Independent Power Producermentioning
confidence: 83%
See 2 more Smart Citations
“…However, in such references a simpler voltage regulator model was used. It can be observed that the results obtained in [10,11] are more oscillatory. This fact was not present in the simulations made here, due to the fact that a more efficient voltage regulator model was used, showing that in previous studies the results obtained had pessimistic responses.…”
Section: Load Rejection At the Independent Power Producermentioning
confidence: 83%
“…In Refs. [10,11] similar simulations were performed. However, in such references a simpler voltage regulator model was used.…”
Section: Load Rejection At the Independent Power Producermentioning
confidence: 98%
See 1 more Smart Citation